Study on Optimalization of Own-Source Revenue in Regencies and Municipals in Central Java Province - Jalu Adi Prakoso; Suci Rahmawati Prima; M. Chrisna Satriagasa; M. Syahli IMNS (Jurnal Ilmu Ekonomi dan Pembangunan, 2016)
Optimizing the management of potential areas would provide additional revenue for the region. This research aims to assess whether the government in the counties and cities in Central Java province has been optimally manage their potentials so as to provide benefits beupa increased local revenues derived from the wealth management area. Through the relationship between the variables of the original income (PAD) and the Gross Domestic Product (GRDP) in the counties and cities in Central Java is expected to be known whether each area has been optimal in obtaining local revenue. The data used is data sekuder form of data revenues and GRDP in counties and cities in the province of Central Java during the years 2011-2013 were berusmber from the Central Statistics Agency (BPS), the Supreme Audit Agency (BPK), Report of Realized APBD, and RPJMD Central Java.Methods of data analysis in this research is to use a simple linear regression analysis (OLS Model) and design analysis group. The analysis showed the existence of ties between the GRDP and the PAD. The magnitude of the relationship analyzed by simple linear regression, where the results indicate a positive trend. That is, there is a directly proportional relationship anatara GRDP and PAD. The coefficient of determination of 99.9% explained that the GRDP variable can be explained by the variable revenue of 99.9%, while 0.1% is explained by other variables.The analysis showed that the GRDP value of the coefficient b> b PAD either at the district, town and overall. These results indicate that there has been no attempt by the government to manage PAD so as to generate the GRDP increase. The government can manage the outcome of PAD to be used in a way that increases the GRDP obtained. As for the test results to determine differences in optimizing the management of local revenue between districts and cities showed that the district can generate GRDP is greater with smaller PAD. It shows that the effort made by the district is more efficient than the effort undertaken by the municipality.Spatial analysis shows a comparison of the GRDP against the PAD in each county and city in Central Java province is divided into four clusters. Each cluster has a distinct regional characteristics seen from economic activity. The results of the socio-economic analysis of the economy in Central Java province when seen from the conditions of employment, which absorbs the most amount of power keraja is in the agricultural sector, which amounted to 31%, followed by the trade sector 22% and industry 19%.Keyword: Decentralization, PAD, GRDP